Crisis Communication Strategy of PT Salim Ivomas Pratama Tbk in Responding to the Alleged Cooking Oil Hoarding Case in 2022 - Muhammad Raihan; Muhammad Alfikri (Jurnal IPTEK Bagi Masyarakat, 2026)
This study examines the crisis communication strategy of PT Salim Ivomas Pratama Tbk in responding to allegations of cooking oil hoarding in 2022, which triggered a reputational crisis amid the national cooking oil shortage. Although the Situational Crisis Communication Theory (SCCT) has been widely applied in crisis communication studies, its application to reputational crises involving strategic food-sector companies in Indonesia remains limited. This study aims to analyze the company's crisis communication strategy from the perspective of SCCT. A qualitative approach with a case study method was employed. Data were collected through document analysis, media observation, online news reports, and official company publications related to the case. The data were analyzed using thematic analysis to identify patterns in the company's communication responses during the crisis. The findings indicate that the company adopted denial and justification strategies by clarifying that the cooking oil stock discovered was part of its internal distribution system rather than an act of illegal hoarding. However, these strategies were not entirely successful in mitigating negative public perceptions due to the high attribution of crisis responsibility and strong media framing. The study suggests that in crises involving essential public commodities, defensive communication strategies should be complemented by transparency, social empathy, and consistent messaging to maintain public trust.